Teaching About Nonmedical Use of Prescription Drugs Among College Students. (October 2019) - Hoyer, Dennis; Correia, Christopher J.
The misuse of prescription medications has emerged as a national public health concern. Epidemiological studies suggest that college students are at an elevated risk to engage in nonmedical use of several medications, including stimulants and central nervous system depressants. Teachers can easily integrate material related to the nonmedical use of prescription drugs (NMUPD) into undergraduate psychology and statistics courses. Presenting this information provides an opportunity for teachers to address fundamental topics in ways that students tend to find interesting and personally relevant. We use this article to introduce a definition of NMUPD, present statistics on prevalence and a wide range of physical and psychological correlates among college students, and discuss risk and protective factors and motives for use. We also present a number of concrete examples of how teachers can use the material to illustrate basic concepts often included in statistics, research methods, and other psychology courses.